Evaluation of XIMIS for Assessing Extreme Pressure Coefficients - Gavanski, Eri; Cook, Nicholas J. (Frontiers in Built Environment, 2019)
Commonly used methods to estimate peak wind pressures on buildings are summarized. The Harris (2009) penultimate XIMIS method is described and calibrated against Gumbel epochal extreme-value analysis (EVA), as well as with the Hermite-Davenport peak factor method by Yang et al. (2013) (YGP) using a very long record of wind tunnel data from many pressure taps. The “industry standard” EVA, comprising 16 ten-minute epochs, gives the best accuracy, but is inefficient in its use of data. YGP is the least accurate, with the largest anomalies underestimating in reattachment zones. XIMIS is comparable to EVA for the same record lengths and remains better than YGP for records up to six times shorter.